COVID-19 on patients with immune-mediated rheumatic disease: a comparative study of disease activity, fatigue, and psychological distress over six months - Claudia Marques; Marcelo M. Pinheiro; Jennifer Lopes; Sandra Lúcia Euzébio Ribeiro; Mary Vânia Marinho de Castro; Lilian David de Azevedo Valadares; Aline Ranzolin; Nicole Pamplona Bueno de Andrade; Rafaela Cavalheiro do Espírito Santo; Nafice Costa Araújo; Cintya Martins Vieira; Valéria Valim; et al. (Advances in Rheumatology)
Abstract Objectives To compare the impact of COVID-19 on the clinical status and psychological distress of patients with immune-mediated rheumatic disease (IMRD) caused by SARS-CoV-2 infection with that of noninfected IMRD controls during a 6-month follow-up period. Methods The ReumaCoV Brazil is a longitudinal study designed to follow IMRD patients for 6 months after COVID-19 (patients) compared with IMRD patients without COVID-19 (controls). Clinical data, disease activity measurements and current treatments regarding IMRD and COVID-19 outcomes were evaluated in all patients. Disease activity was assessed through validated tools at inclusion and at 3 and 6 months post-COVID-19. Fatigue, using FACIT-F (Functional Assessment of Chronic Illness Therapy) and psychological distress, using DASS 21 (Depression, Anxiety and Stress Scale − 21 Items), used to evaluated psychological distress, were evaluated at 6 months after COVID-19 in both groups. The significance level was set as p < 0.05, with a 95% confidence interval. Results A total of 601 patients were evaluated—321 patients (IMRD COVID-19 + patients) and 280 controls (IMRD COVID-19- patients)—who were predominantly female with similar median ages. Disease activity assessment over a 6-month follow-up showed no significant difference between cases and controls. Although the mean activity scores did not differ significantly, some patients reported worsened disease activity post-COVID-19, particularly in rheumatoid arthritis (RA) (32.2%) and systemic lupus erythematosus (SLE) patients (23.3%). Post-COVID-19 worsening in RA patients correlated with medical global assessment (MGA) and CDAI scores, with a moderate to large effect size. Diabetes mellitus showed a positive association (OR = 7.15), while TNF inhibitors had a protective effect (OR = 0.51). Fatigue, depression, anxiety, and stress were significantly greater in patients than in controls. Worse disease activity post-COVID-19 correlated with worse FACIT-F and DASS-21 scores in RA patients. No significant associations were found between COVID-19 outcomes and post-COVID-19 disease activity, FACIT-F or DASS-21. Conclusions Post-COVID-19 IMRD patients exhibited significant fatigue, depression, anxiety, and stress, which can be mistaken for disease activity, despite having similar disease activity scores. The variability in reports on IMRD flares and the potential triggering of SARS-CoV-2 for autoimmune manifestations underscore the need for detailed clinical assessment and a comprehensive approach to managing them.